The Oxylipin Pathways: Biochemistry and Function - Wasternack, Claus; Feussner, Ivo (Annual review of plant biology, 2018)
Plant oxylipins form a constantly growing group of signaling molecules that comprise oxygenated fatty acids and metabolites derived therefrom. In the last decade, the understanding of biosynthesis, metabolism, and action of oxylipins, especially jasmonates, has dramatically improved. Additional mechanistic insights into the action of enzymes and insights into signaling pathways have been deepened for jasmonates. For other oxylipins, such as the hydroxy fatty acids, individual signaling properties and cross talk between different oxylipins or even with additional phytohormones have recently been described. This review summarizes recent understanding of the biosynthesis, regulation, and function of oxylipins.
Keywords: Stress, Physiological; oxylipiny; Lipoxygenase; CYP74; lipid signaling; signální transdukce; Signal Transduction; Cyclopentanes; cyklopentany; fyziologický stres; homeostáza; Homeostasis; jasmonates; lipoxygenase pathway; wound response; lipid peroxidation; Oxylipins; lipoxygenasa